(untitled) (Ustozlar uchun, 2025)
The translation of historical texts is one of the most complex and responsible areas within the field of translation studies. It requires not only linguistic competence but also profound knowledge of history, culture, and the socio-political background of the original era. This paper explores the main theoretical approaches to the translation of historical documents and literary sources, focusing on both global and Uzbek scholarly contributions. The study emphasizes the challenges of translating archaic language, idiomatic expressions, and culturally specific concepts. Furthermore, it discusses the strategies applied by translators to preserve the authenticity and readability of historical texts.